(3GdGfJUGQ aj PcQ CMhGd bGeY GdeHJOYjf hBNQ GdeLJgOjfs - (3YHO GdQMef Hf ESeGYjd Hf EHQGgje GdebOSj GdOeTbqj, CHh GdbGSe, TgGH GdOjf, CHh TGeI,J (B665 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg fHPg jSjQg eNJUQg ai PcQ MGd SjOfG TjNfG TjN GdESdGe Jbi GdOjf CHj GdYHGS CMeO Hf JjejI QVi Gddg Yfg s
(3BNQgG (B:s
(3hBQGO GdTjN Cf jJcde ade jecf ef GdHMK hGdcdGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B125s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B34 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B666s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs